1996
DOI: 10.4315/0362-028x-59.8.795
|View full text |Cite
|
Sign up to set email alerts
|

Use of Novel Polymerase Chain Reaction Primers for the Specific Detection of Heat-Labile Toxin I, Heat-Stable Toxin I and II Enterotoxigenic Escherichia coli in Milk

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains which produce heat-labile and/or heat-stable toxins (LT and ST) have been some of the most important microorganisms causing food- and waterborne diseases. Rapid and sensitive methods for the specific detection of enterotoxigenic E. coli are thus important. Although quite a few polymerase chain reaction (PCR) primers have been developed for the specific detection of ETEC genes coding for LT I, ST Ia, and ST Ib, only a few primers have been designed for the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In particular, the polymerase chain reaction (PCR) has been used successfully for the detection of Escherichia coli O157:H7, Listeria monocytogenes and Bacillus spp. in milk and other dairy products (Lantz et al 1994a;Candrian 1995;Dickinson et al 1995;Fratamico et al 1995;Herman et al 1995;Tsen et al 1996;Herman et al 1997). Many food components, however, are inhibitory to PCR, by either interfering with cell lysis (i.e., DNA extraction), contributing to nucleic acid degradation or inhibiting Taq DNA polymerase (Rossen et al 1992;Herman and De Ridder 1993;Powell et al 1994;Bickley et al 1996;Wilson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the polymerase chain reaction (PCR) has been used successfully for the detection of Escherichia coli O157:H7, Listeria monocytogenes and Bacillus spp. in milk and other dairy products (Lantz et al 1994a;Candrian 1995;Dickinson et al 1995;Fratamico et al 1995;Herman et al 1995;Tsen et al 1996;Herman et al 1997). Many food components, however, are inhibitory to PCR, by either interfering with cell lysis (i.e., DNA extraction), contributing to nucleic acid degradation or inhibiting Taq DNA polymerase (Rossen et al 1992;Herman and De Ridder 1993;Powell et al 1994;Bickley et al 1996;Wilson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of specific nucleic acids in these products allows the determination of the presence or absence of certain ingredients or contaminants as well as the identification of specific characteristics of single components (7,32,35). DNA-based detection systems for genetically modified foods (17,21,22,24,25,31,53) and food-borne pathogens (1,2,21,27,51,55), including mycotoxin-producing fungi (6,8,9,18,42,47), have been developed recently. Furthermore, the detection of plant and animal species in the final food products has been shown to be feasible with DNA-based methods (33,34).…”
Section: Nucleic Acid-based Techniquesmentioning
confidence: 99%
“…However, it was found that although the novel PCR primers for SLTI and SLTII genes detection have melting temperatures similar to those of the LTI and STII genes specific primers reported previously (Tsen et al 1996) i.e. 60°C vs 62°C, these primers could not be combined into a multiplex system for the simultaneous detection of the SLTI, SLTII, LTI and STII genes of E. coli cells.…”
Section: Multiplex Pcr System and Its Detection Sensitivitymentioning
confidence: 75%
“…Also, it should be mentioned that although a multiplex system that detects all types of ETEC (including STI, STII, LTI, and LTII E. coli) and STEC (including SLTI and SLTII E. coli) may be more useful, the simultaneous detection of any four, or more than four, genes has not been reported. Although we tried to combine the STI gene specific primers reported by us (Tsen et al 1996) or by Schultsz et al (1994) into out multiplex PCR system, the attempt was unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation